Tough hydrogels with tunable soft and wet interfacial adhesion - Yikun Zhang (Elsevier, 2021)
Hydrogels that possess adequate toughness in bulk and at soft interface are highly desirable. We report a fully physically crosslinked dual Amylopectin (Amy, the first network)/poly(N-hydroxyethyl acrylamide) (PHEAA, the second network) hydrogel, where both networks were hydrogen bonding (H-bonding) crosslinked, with super toughness in bulk and tunable adhesion at hydrogel-soft tissue interface. Through adjustment of hydrogen bond density, strong and tough hydrogels were prepared that exhibited different levels of adhesion strength and three adhesive failure mechanisms. We replaced Amy with oxidized starch (OSA) to synthesize dual and hybrid chemically/physically crosslinked OSA/PHEAA double network (DN) hydrogels that were capable of forming Schiff's bases at hydrogel-hydrogel or hydrogel-tissue interfaces, aside from interfacial H-bonding, incurring sustained, high interfacial toughness (1850 J m−2 hydrogel-hydrogel and 610 J m−2 hydrogel-tissue) in wet environments. Such tough and adhesive DN hydrogels have great potential in various applications such as engineering of artificial soft tissues or implantable devices that are intended to adhere to internal organs or tissues.